Usefulness, feasibility and face validity of the interRAI Palliative Care instrument according to care professionals in nursing homes: A qualitative study. (October 2016) - Hermans, Kirsten; Spruytte, Nele; Cohen, Joachim; Van Audenhove, Chantal; Declercq, Anja
Abstract: Background: Nursing homes are important locations for palliative care. High quality palliative care requires an evaluation of the different care needs of the nursing home residents. The interRAI Palliative Care instrument is a comprehensive assessment that evaluates the needs and preferences of adults receiving palliative care. Objectives: This study aims to evaluate the usefulness, feasibility and face validity of the interRAI Palliative Care instrument. Design: A qualitative study was conducted, based on the abductive reasoning approach. Setting: Fifteen nursing homes in Flanders (Belgium). Participants: Calls for participation were sent out by four umbrella organizations of Flemish nursing homes (Belgium) and at a national conference for nursing home staff. Nineteen care professionals (nurses, certified nursing assistants, psychologists, physiotherapists, quality coordinators and directors) of 15 nursing homes voluntarily agreed to participate in the study. Methods: During one year, care professionals evaluated the needs and preferences of all nursing home residents receiving palliative care by means of the interRAI Palliative Care instrument. Data on the usefulness, feasibility and face validity of the interRAI Palliative Care instrument were derived from notes, semi-structured interviews and focus groups with participating care professionals and were thematically analyzed and synthesized. Data were gathered between December 2013 and March 2015. Results: In general, the interRAI Palliative Care (interRAI PC instrument) is a useful instrument according to care professionals in nursing homes. However, care professionals made a series of recommendations in order to optimize the usefulness of the instrument. The interRAI PC instrument is not always feasible to complete because of organizational reasons. Furthermore, the face validity of the instrument could be improved since certain items are incomplete, lacking, redundant or too complex. Conclusions: Findings highlight the importance of adapting the content of the interRAI Palliative Care instrument for use in nursing homes. Furthermore, the use of the instrument should be integrated in the organization of daily care routines in the nursing homes. Tackling the critical remarks of care professionals will help to optimize the interRAI Palliative Care instrument and hence support palliative care of high quality in nursing homes.